Changing Borders and Challenging Belonging - Grote, Georg; Carlà, Andrea (2024)
«This timely and important book provides a critical look at borders and belonging. It illuminates the tensions and contradictions that often exist within the logic of legal and political mechanisms that define regional and national boundaries and the reality of the lives lived within these constructions. The resulting essays are instructive, thought-provoking and sometimes very moving explorations of the making and meaning of historical and contemporary borderlands.» (Roisín Higgins, Professor of History, National University of Ireland Maynooth) «This volume is a masterful combination of analyses of feelings of belonging and identities following from changing state and cultural borders in the past and present and their challenges for living together. Its chapters analyse the intersections of people, territory, institutions and law from theoretical perspectives as well as through reflexive individual experience of social identity formation from below, often with a focus on their contestation in (re-)territorialized sub-state regions.» (Josef Marko, Professor of Comparative Public Law and Political Sciences, University of Graz) Both the Brexit process and the Covid pandemic have challenged the idealistic concept that borders in Europe and elsewhere were becoming ever more permeable. The idea that the world was becoming a global village has been seriously eroded. Meanwhile, the war in Ukraine has once again highlighted how power politics draws borders and shapes belongings. This has necessitated analyses of the nature of human-made borders and boundaries and the consequences for individuals and collectives who experience inclusion or exclusion on their feelings of belonging and their identities. Similarly, governmental policies within states have created majorities and minorities and have caused grave implications for those groups at the receiving end of legislation and state actions. This multidisciplinary volume comprises essays from researchers and academics, located in Europe and beyond, who investigate the effects of border creation, social and legal inclusivity and exclusion on individuals and collective identities in the past and today. Combining «from above» and «from below» perspectives, the volume explores macro-political processes affecting borders and senses of belonging as well as their intersections at the microlevel, including private views and individual responses to such types of processes.